2022
DOI: 10.3389/fphar.2022.771083
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Future Prescribers About Antimicrobial Resistance and Their Preparedness Towards Antimicrobial Stewardship Activities in Pakistan: Findings and Implications

Abstract: Background: Insufficient antimicrobial-related training for physicians during their undergraduate education could have a negative impact on their prescribing. Unlike previous studies, this study not only explored the understanding and perception of Pakistani medical students about antibiotics and resistance, but also their preparedness towards antimicrobial stewardship programs.Methods: An online cross-sectional study was undertaken with final-year medical students using a validated questionnaire from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
8
1
Order By: Relevance
“…This is contradictory to a study in Central India on the knowledge, attitude and where 94% of the respondents were aware that bacteria were not responsible for causing colds and influenza [17] and another study in Pakistan which reported that of 83.5% responding medical students were aware of the ineffectiveness of antibiotics against viral infections [18]. However, a study in Egypt reported findings similar to our study where 36% of the medical students thought that bacteria cause common cold and influenza [19].…”
Section: Comparison With the Existing Studiescontrasting
confidence: 77%
“…This is contradictory to a study in Central India on the knowledge, attitude and where 94% of the respondents were aware that bacteria were not responsible for causing colds and influenza [17] and another study in Pakistan which reported that of 83.5% responding medical students were aware of the ineffectiveness of antibiotics against viral infections [18]. However, a study in Egypt reported findings similar to our study where 36% of the medical students thought that bacteria cause common cold and influenza [19].…”
Section: Comparison With the Existing Studiescontrasting
confidence: 77%
“…We are aware that previous studies have been undertaken among HCWs in the different regions of Pakistan, including physicians and pharmacists as well as medical and pharmacy students, to ascertain key aspects regarding antibiotics use, AMR, and ASPs [ 38 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. However, we are unaware of any studies that have been conducted to fully evaluate knowledge of antibiotic use, AMR, and ASPs among pharmacy technicians serving specifically in ambulatory care facilities.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that this is the first paper in Pakistan that has evaluated the different perspectives of antibiotic use, AMR and ASPs among future medical doctors, pharmacists and nurses among both public and private sector institutions in Pakistan. We are aware that studies have been published with different student cohorts across LMICs including Pakistan; however, we are unaware of any studies that have combined all three key student populations among both public and private universities in LMICs [69,70,[72][73][74][75][76][77][78][79][80][81][82][83]. This is increasingly important, with multidisciplinary teams being key to improving future antibiotic prescribing as part of ASPs [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the WHO has stressed that awareness, training, appropriate use, diagnostic stewardship and surveillance, as well as coordination among HCWs, is necessary to combat rising AMR rates [68]. To date, only a few studies have been conducted among medical and pharmacy students in Pakistan about their awareness concerning antibiotic use, AMR and ASPs [69,70]. The current study aimed to address this by evaluating the knowledge of antibiotic use and AMR, and the preparedness towards ASPs, among final year medical, pharmacy and nursing students from Punjab Province in Pakistan.…”
Section: Introductionmentioning
confidence: 99%